Demographic characteristics of chronic pancreatitis patients in the era of endosonography: Experience of a single tertiary referral center in Turkey - Şişman, Gürhan; Köroğlu, Emine; Erzin, Yusuf; Hatemi, İbrahim and Tuncer, Murat and Şentürk, Hakan (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: There are no clinical data available about chronic pancreatitis (CP) on a series of patients of sufficient number in Turkey. In this study, the etiology and clinical features of CP were evaluated in one center, which is a tertiary referral hospital. Materials and Methods: The files of 168 patients who had been diagnosed with CP in our Medical Faculty between October 2007 and May 2013 were retrospectively analyzed. The etiological factors, symptoms, complications, and treatment methods were analyzed. Results: The most common etiological factor was alcohol abuse (39%). The average age±SD was 46±15.2 years, and the male:female ratio was 4.2:1 (it was 2.6:1 for other etiologies except alcohol abuse and 15.5:1 in alcoholic CP patients, p<0.05). The most frequent complication was diabetes mellitus (44%). The smoking rate was significantly higher in CP patients with pancreatic calcification (p<0.05). One-third of the patients received various types of endoscopic treatment. During a mean follow-up period of 42±13 months (range, 6–55), pancreatic cancer was detected in four patients (2.3%). Conclusion: In majority of the CP patients, the etiology is alcohol abuse in Turkey. The development of diabetes is the most frequent complication of CP, which is independent of the etiology.